Pendidikan Da’i dan Proses Pelaksanaannya - Shofiyah, Shofiyah (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2015)
So that the da'wah can be accepted by mad'unya, then the process of da'wah that must be implemented in order to transform the teachings of the Islamic religion needs to get a more serious study, so that proselytizing process carried out to get sympathy from mad'u which in the end consciously to be in give as a consequence islamic. Grown against science and technology also impact on take against the treatment of religious teachings for its adherents. The phenomenon of life problems will be given priority in the delivery of missionary mission itself. Basically that dakwah that can be accepted by the mad'unya is that can provide solutions in life. The need for added values ​​for the da'i is that the other sciences that support the activities of da'wah process will be a priority consideration for the da'i to improve the quality of delivery and success of da'wah.